APPLICATIONS TREND LINEAR FORECASTING USING TOTAL ANNUAL PRODUCTION TURBO PASCAL PROGRAMMING LANGUAGE - Rachman Handy Prasetyo; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2005)
method can dperkirakan total production for the coming year. Production data forprevious years were analyzed by calculating the trend values in each year. For thatvalue can be used with this trend linear trend equation, namely:Yt = a + btWhere: Yt = Total production of goods (in thousands of units)a = Constantb = Coefficientt = t YearsThe value of a (constant) and b (coefficient) was first found using the formula. Fromthe linear trend equation obtained calculated value of production per year trend byentering the value of coding each year in the linear trend equation. To predict the totalproduction of goods in advance of next year searchable presenrase value than thetrend (SR) each year by using the formula:Percent rather than trend = Yi / Yt x 100%Then count the number of SR and SR average. Using the average value of SR into thelinear equation, it can be predicted rend production next year, namely:Yt = (a + bt) * average SR